Pengaruh Harga, Kualitas Produk dan Kualitas Pelayanan terhadap Kepuasan Pelanggan (Studi pada Aki Incoe PT Meka Adipratam di Kota Semarang) - Triongko, Budi; Widodo, Untung; Widowati, Maduretno (STIE PENA, 2022)
This study aims to determine whether Price, Product Quality and Service Quality have an affect on Customer Satisfaction study on Incoe battery PT Meka Adipratama at Semarang.This research is a survey research. The population in this study were customers from PT Meka Adipratama. The size of the research sample taken was 75 people determined by the Slovin formula. Sampling was carried out using the purposive sampling method, which is a sampling method with certain criteria. The method of analysis using descriptive analysis, classical assumption test includes normality test, multicollinearity test and heteroscedasticity test. Hypothesis testing in this study used multiple linear regression analysis and hypothesis testing with the help of SPSS. The results of this study indicate that Price has a positive and significant effect on Customer Satisfaction, Product Quality has a positive and significant effect on Customer Satisfaction, Service Quality has a positive and significant effect on Customer Satisfaction. Price, Product Quality and Service Quality simultaneously have a positive and significant effect on Customer Satisfaction on Incoe battery PT Meka Adipratama at Semarang. Keywords: Price, Product Quality, Service Quality, Customer Satisfaction.